Strategi Kepala Madrasah Ibtidaiyah Dalam Pengupayaan Madrasah Literasi - Muchammad Mahfudi (THE JOER: Journal Of Education Research, 2023)
Literacy is the ability to find, observe, understand and communicate information that is owned by each individual to improve the quality of life in a sustainable manner. At the elementary school level, literacy is a basic need that must be grown. This literacy growth can be realized through the Madrasah Literacy Movement through daily activities organized by the school in stages.. The literacy movement carried out by schools refers to the literacy movement guidelines that have been compiled and determined by the Directorate General of Primary and Secondary Education of the Ministry of Education and Culture. The aim of this research is: (1) Describe the strategy of the head of school in development Literacy Madrasah in the MI Taufiqul Hidayah Randubango. (2) Analyzing the implementation of madrasah principals in the Implementation of Literacy Madrasah in the MI Taufiqul Hidayah Randubango. (3) Analyzing the constraints in the implementation of Literacy Madrasah in the MI Taufiqul Hidayah Randubango. This research uses descriptive qualitative research. In this study, researchers are actively involved and go directly to the field to understand the phenomenon and maintain the naturalness of the data. The techniques used by researchers to collect data are interviews, observation, and documentation. In addition, data analysis is carried out through data reduction, data presentation, and drawing conclusions. Furthermore, to check the validity of the research data using repeated observations, triangulation of sources and peer discussion. The results of the study show that: Principal's Strategy in Developing Madrasah Literacy in the MI Taufiqul Hidayah 1. The literacy madrasah development strategy is as follows: 1) KKG mini meeting and 2) make literacy class. 3) literacy program preparation, 4) classroom facility management 5) arrange RPP, 6) make a schedule of activities, 7) Reading corner management. Implementation of the Head of Madrasah Strategy in Madrasah Literacy Development in MI Taufiqul Hidayah The implementation of literacy madrasa development is as follows: 1) Routine activities are a) read tahlil on thursday, b) dhuha and dhuhur prayers in congregation Monday to Thursday c) the habit of reading Asma'ul Husna and singing national songs d) qiro'ah in the mosque on Friday and, e) istiqosah saturday. f), program 1 semester 1 book.g) Read a book about 15 minutes, h) activities responding to reading books, i) penggunaan sudut baca. 2) Incidental activities. 2. Barriers to Madrasah Literacy Development in the MI Taufiqul Hidayah Randubango as follows: 1) procurement or funding for new books, 2) limited number of reading books, especially textbooks, 3) newly renovated library room and still need additional reference books, 4) low interest in reading.